2022
DOI: 10.1186/s12889-022-14122-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of obesity-related indicators for identifying metabolic syndrome among normal-weight adults in rural Xinjiang, China

Abstract: Background This study aimed to compare the ability of certain obesity-related indicators to identify metabolic syndrome (MetS) among normal-weight adults in rural Xinjiang. Methods A total of 4315 subjects were recruited in rural Xinjiang. The questionnaire, biochemical and anthropometric data were collected from them. Binary logistic regression was used to analyze the association between the z-score of each index and MetS. The area under the recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Compared with TG and FBG, the TyG index has better predictive power for predicting MetS [ 28 ]. Various studies have confirmed the predictive ability of the TyG index for MetS [ 9 , 13 15 , 29 ]. Fernández-Aparicio et al investigated the ability of atherogenic indices to predict MetS in Spanish adolescents and found that the TyG index had the greatest AUC in males and the TyG index and LDL-c/HDL-c had the greatest AUCs in females [ 9 ].…”
Section: Discussionmentioning
confidence: 94%
“…Compared with TG and FBG, the TyG index has better predictive power for predicting MetS [ 28 ]. Various studies have confirmed the predictive ability of the TyG index for MetS [ 9 , 13 15 , 29 ]. Fernández-Aparicio et al investigated the ability of atherogenic indices to predict MetS in Spanish adolescents and found that the TyG index had the greatest AUC in males and the TyG index and LDL-c/HDL-c had the greatest AUCs in females [ 9 ].…”
Section: Discussionmentioning
confidence: 94%
“…The bivariate boxplot for male (Supplementary Fig. 7A) revealed six study outliers [ 40 , 42 , 44 , 54 , 60 , 62 ] and the bivariate boxplot for female (Supplementary Fig. 7B) showed ten study outliers [ 40 , 43 , 44 , 46 , 58 , 60 , 64 , 65 , 78 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cardiovascular metabolic risks in individuals with normal BMI are often overlooked 27 . Research indicates that individuals with a normal weight but unhealthy metabolism have an increased risk of diabetes and cardiovascular diseases by 1.5 to 2 times 28,29 .…”
Section: Introductionmentioning
confidence: 99%